High-Resolution 3D-constructive interference in steady-state MR imaging and 3D time-of-flight MR angiography in neurovascular compression: A comparison between 3T and 1.5T - Dörfler, Arnd; Garcia, M.; Naraghi, Ramin; Zumbrunn, T.; Roesch, J.; Hastreiter, Peter (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: High-resolution MR imaging is useful for diagnosis and preoperative planning in patients with NVC. Because high-field MR imaging promises higher SNR and resolution, the aim of this study was to determine the value of high-resolution 3D-CISS and 3D-TOF MRA at 3T compared with 1.5T in patients with NVC. MATERIALS AND METHODS: Forty-seven patients with NVC, trigeminal neuralgia, hemifacial spasm, and glossopharyngeal neuralgia were examined at 1.5T and 3T, including high-resolution 3D-CISS and 3D-TOF MRA sequences. Delineation of anatomic structures, overall image quality, severity of artifacts, visibility of NVC, and assessment of the SNR and CNR were compared between field strengths. RESULTS: SNR and CNR were significantly higher at 3T (P < .001). Significantly better anatomic conspicuity, including delineation of CNs, nerve branches, and assessment of small vessels, was obtained at 3T (P < .02). Severity of artifacts was significantly lower at 3T (P < .001). Consequently, overall image quality was significantly higher at 3T. NVC was significantly better delineated at 3T (P < .001). Six patients in whom NVC was not with certainty identifiable at 1.5T were correctly diagnosed at 3T. CONCLUSIONS: Patients with NVC may benefit from the higher resolution and greater sensitivity of 3T for preoperative assessment of NVC, and 3T may be of particular value when 1.5T is equivocal.
CRIS-Team Scopus Importer:2022-08-05